2004
DOI: 10.1016/j.tet.2004.05.086
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antitumor activities of glucan derivatives

Abstract: Abstract-A highly efficient and practical method for the preparation of]-D-Glc-OMe was described. A dendritic nonasaccharide was also synthesized. The antitumor activities of hexasaccharide, the dendrimer, their sulfated derivatives, together with the natural glucan -protein and the corresponding polysaccharide isolated from barmy mycelium of Grifola frondosa, were preliminarily investigated based on Sarcoma-180 studies in mice tests. Our results suggest that the sulfated branching oligosaccharide and natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
11
2
1
Order By: Relevance
“…It is interesting to note that certain sulfated oligosaccharides showed antitumor activity in a sarcoma-180 mouse model. 27 This is in contrast to the potent proangiogenesis activity in the CAM and in the 3D-ECS for sulfated oligosaccharides, as shown in this report. The effect on tumor weight based on the study design 27 cannot be explained and is difficult to ascertain because of the lack of details about the model.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…It is interesting to note that certain sulfated oligosaccharides showed antitumor activity in a sarcoma-180 mouse model. 27 This is in contrast to the potent proangiogenesis activity in the CAM and in the 3D-ECS for sulfated oligosaccharides, as shown in this report. The effect on tumor weight based on the study design 27 cannot be explained and is difficult to ascertain because of the lack of details about the model.…”
Section: Discussioncontrasting
confidence: 69%
“…27 This is in contrast to the potent proangiogenesis activity in the CAM and in the 3D-ECS for sulfated oligosaccharides, as shown in this report. The effect on tumor weight based on the study design 27 cannot be explained and is difficult to ascertain because of the lack of details about the model. The study performed by Du et al 27 focused on the chemistry aspects and did not clearly provide a detailed description of the model; the effect on sarcoma tumor weight was marginal at doses ranging from 2.5 to 10 mg/kg.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Therefore, molecular modification and structure improvement of polysaccharides are a hot topic in recent years. Many studies have demonstrated that biological activities of polysaccharides are increased by molecular modification [3,7,8,21].…”
Section: Introductionmentioning
confidence: 99%